The impact of the French New Economic Regulations Law on the disclosure of corporate environmental strategies. A longitudinal study of the retail industry in France. - Redon, Thémis (2010)
In the literature on corporate environmental strategy, the question of how environmental strategies of companies evolve over time remains little explored. As a result, the purpose of this paper is to understand the evolution of corporate environmental strategies of a sample of French retailers from 2000 to 2009, period that extends to the pre and post implementation of the French New Economic Regulations (NRE) law of 2001. This regulatory context is particularly interesting because France adopted a peculiar legislation. Contrary to other European laws, the French NRE law does not prescribe new social or environmental requirements but only informational requirements.